LINK OF Pharella acutidens ABUNDANCE AND MANGROVE HABITAT IN CEMPI BAY, DOMPU REGENCY, WEST NUSA TENGGAR - Awan Dermawan; Isdradjat Setyobudiandi; Majariana Krisanti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Pharella acutidens clam is a bivalve lives in mangrove ecosystem substrate, that is one of protein source for Dompu’s people. the existence of pharella acutidens in Cempi Bay, Dompu begin difficult to collect due to mangrove area has been reduced by result of land conversion from mangrove ekosistem area to estuary aquaculture pond and mangrove timber exploitation by local community as well as the Pharella acutidens routin exploitation, these factor may has influenced the existence of Pharella acutidens clam in the Cempi Bay mangrove ecosystem. This study aims to determine the condition of the Pharella acutidens clams located in the mangrove ecosystem Cempi bay, which in is an abundance on different conditions mangrove vegetation an abundance of Pharella acutidens clams tended more on high density and high basal area sites as well as the size of the clams. Varied habitats, from the density of 1.333 trees/ha up to 3.300 trees/ha, the basal area and the diverse species of mangrove, making this study an interesting thing  This journal is part of the research that explains positive influence between total basal area of mangrove vegetation (∑Ci) and abundance of Pharella acutidens, by simple regression analysis. The result showed that total basal area of mangrove vegetation (∑Ci) positively influencing abundance of P. acutidens clams with equation y = 0,3038x + 3,887 and R2 = 0,9579.